Comparative evaluation of suturing technique following tenorrhaphy of superficial digital flexor tendon in calves : Clinical and fasciagraphic studies - GUPTA, O P; KUMAR, NAVEEN; SINGH, G R; SHARMA, A K (The Indian Journal of Animal Sciences, 2013)
Tenorrhaphy of completely served superficial digital flexor was performed by Bunnell-Mayer andÂ· Locking loop technique using silk, in 5 and 6 calves respectively. Clinical and fasciagraphic observations revealed better healing by the Bunnell-Mayer technique.